Mauritania Engaging the Private Sector in Education : SABER Country Report 2016 - Wesley, Hugo (World Bank, Washington, DC, 2017)
This report presents an analysis of how effectively the current policies in Mauritania engage the private sector in basic (primary and secondary) education. The analysis draws on the engaging the private sector (EPS) framework, a product of the World Bank’s systems approach for better education results (SABER). SABER-EPS research in Mauritania found that despite impressive gains in increasing enrollment and achieving gender parity at the primary level, access to post-primary schooling remains low, and ensuring equity in education is a challenge. School providers in Nepal include institutional schools, which are private, and community schools that receive government funding. Based on a review of existing policies SABER-EPS offers the following recommendations for Mauritania to enhance private sector engagement in education to meet the challenges of access, quality, and equity: (1) improve the regulatory environment to support a greater supply of post-primary schools in underserved areas; (2) strengthen accountability measures, including regularly collecting and disseminating comparable information on school performance, while increasing school autonomy; and (3) consider providing additional support to poor and marginalized students attending independent schools and post-primary schooling. The report provides an overview of SABER-EPS, followed by a description of the basic education system in Mauritania, with a focus on the private sector and government policies related to private provision of education. The report then benchmarks Mauritania’s policy environment utilizing the SABER-EPS framework, and offers policy options to enhance learning for all children in primary and secondary school.